Implementasi Permainan Ular Tangga Raksasa dalam Mengembangkan Kognitif Anak Usia Dini - Vinda Ayu Prihatini; Mursid Mursid (Journal of Early Childhood and Character Education, 2022)
This study discusses the implementation of the giant snake and ladder game in developing the cognitive development of early childhood group B at RA Harapan Ummi, Semarang City in the 2021/2022 academic year which includes the implementation of the giant snake and ladder game in developing cognitive and also about the supporting factors and inhibiting factors for the implementation of the snake and ladder game. giant. This research is motivated because the problems of early childhood development in group B at RA Harapan Ummi have not developed optimally.This study uses a descriptive qualitative research method, where the author makes a factual, accurate and systematic description of the event being studied. Data collection techniques from this study were carried out by observation, interviews and documentation.The results of this study indicate that the implementation of the giant snake and ladder game in developing the cognitive development of early childhood group B at RA Harapan Ummi, Semarang City has been successful. Supporting factors include: the availability of facilities and infrastructure that is quite complete at RA Harapan Ummi, Semarang city, making it easier for students to learn, the use of educational game tools in the form of a giant snake and ladder and practiced directly, collaboration between educators and parents to discuss children's development. and the inhibiting factor is the presence of children who are hyperactive and interfere with other friends while playing.